2005
DOI: 10.1126/science.1112181
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Trypanosomatid Parasitic Protozoa

Abstract: A comparison of gene content and genome architecture of Trypanosoma brucei, Trypanosoma cruzi, and Leishmania major, three related pathogens with different life cycles and disease pathology, revealed a conserved core proteome of about 6200 genes in large syntenic polycistronic gene clusters. Many species-specific genes, especially large surface antigen families, occur at nonsyntenic chromosome-internal and subtelomeric regions. Retroelements, structural RNAs, and gene family expansion are often associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
615
3
30

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 723 publications
(666 citation statements)
references
References 37 publications
18
615
3
30
Order By: Relevance
“…Ultimately, 41 chromosomes were assembled, which is well above the predicted number of T. cruzi chromosomes based on the early studies of pulsed-field gel electrophoresis analyses (Cano et al 1995, Vargas et al 2004. Although separated by hundreds of millions of years of evolution, genome organisation in T. cruzi is largely syntenic with the other two trypanosomatid genomes, collectively known as the Tri-Tryp genomes (T. brucei and L. major), and most of the species-specific genes, such as large surface protein gene families, occur at non-syntenic chromosome-internal and subtelomeric regions (El-Sayed et al 2005b).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, 41 chromosomes were assembled, which is well above the predicted number of T. cruzi chromosomes based on the early studies of pulsed-field gel electrophoresis analyses (Cano et al 1995, Vargas et al 2004. Although separated by hundreds of millions of years of evolution, genome organisation in T. cruzi is largely syntenic with the other two trypanosomatid genomes, collectively known as the Tri-Tryp genomes (T. brucei and L. major), and most of the species-specific genes, such as large surface protein gene families, occur at non-syntenic chromosome-internal and subtelomeric regions (El-Sayed et al 2005b).…”
mentioning
confidence: 99%
“…Heterogeneous arrays as large as 600 kb for genes that encode surface proteins were found to be clustered in the T. cruzi genome (El-Sayed et al 2005b). In addition, long terminal repeat (LTR) and non-LTR retro-elements as well as other subtelomeric repeats accounted for the large proportion of repetitive sequences (50%) in this genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…L. major, T. brucei and T. cruzi contain about 32.8, 26 and 55-megabase size haploid genomes distributed in 36, 11 and 28 chromosomes with an average GC-content of 59.7%, 46.4% and 51%, respectively. Comparative analyses [1] revealed that the three genomes share 6158 ortholog clusters of protein-coding genes, which exist in large syntenic blocks containing 80% of the T. brucei and 93% of the L. major genes. They also share a number of molecular and biochemical characters [7].…”
Section: Introductionmentioning
confidence: 99%
“…Una de las estrategias desarrolladas para la bús-queda de nuevos medicamentos consiste en el modelado o reconstrucción de vías metabólicas importantes que faciliten análisis bioquímicos detallados en el organismo de interés, permitiendo así la identificación de posibles blancos moleculares específicos para estos medicamentos (2)(3)(4). Los resultados obtenidos en los últimos años en la exploración de la vía del metabolismo del fosfatidil-inositol la postulan como una alternativa en el desarrollo de medicamentos para diversas enfermedades, incluida la leishmaniasis (5)(6)(7)(8)(9).…”
unclassified